(untitled) (Eurasian Research Bulletin, 2023)
Today, the problem of providing the population with high-quality food proteins remains relevant, soybean is recognized as the main source of protein nutrition for the population in the world. The use of soybean processing products in the food industry poses the task of developing modern methods or creating a new methodology for qualitative and quantitative determination of soy content in food products.